A dashboard proposal for pre-scheduling elective orthopedic surgeries in Brazil - Aparecido Carlos Duarte; Jair Minoro Abe; Liliam Sayuri Sakamoto (Global Journal of Ecology - Peertechz Publications, 2023)
The procedure for receiving materials from the CME - Material and Sterilization Center, begins after the surgery is released by the agreement together with the approval of the supplier, once this is approved, the delivery of the materials to be used in the hospital will commence. This delivery may take place hours or even a day before the scheduled date since the materials need to be washed and sterilized, and in some cases, there is a lack of a certain instrument that may cancel or even postpone the surgery that is only identified when the articles are opened while in the operating room and even with the patient undergoing anesthetic induction, bringing inconvenience to the patient, the medical team and the hospital. In this article we will be proposing the construction of a Dashboard to help reduce the errors or problems encountered during the scheduling of surgeries to be performed in Hospitals in Brazil, we are only dealing with Elective surgeries, those schedules that depend on third-party materials for their performance.